Workability Study for Graduates of the Faculty of Engineering Universitas Negeri Surabaya - Arizal, Heru; Wiyono, Agus; Mulyono, Wahyu Dwi; Mayasari, Peppy (LPPM Universitas PGRI Semarang, 2025)
A successful education provider is one that produces graduates who can apply their knowledge and skills in the real world. This study aims to examine the 2022 graduate profile through a tracer study and identify factors that influence their competencies. Using a descriptive quantitative approach, the study involved 471 graduates from 13 study programs at the Faculty of Engineering. Data collection techniques using questionnaires and analyzed using factor analysis with the help of SPSS. Results show that the average waiting time for graduates to secure their first job is 4.28 months. Most alumni reported that their jobs were very closely (31%) or closely (30%) related to their field of study. The study identified 27 competency-supporting factors, which were grouped into two main components through factor analysis. Combined, these components influence alumni competence by 68.056%. The findings indicate that the curriculum and graduate profile developed by the study programs remain relevant to industry needs. Therefore, universities should adopt a holistic educational approach that balances academic knowledge with character development, ethics, and soft skills. Strengthening collaboration with industry and continuously updating the curriculum are key steps to ensure graduates stay relevant and competitive in the job market.